Handbuch der österreichischen Kinder- und Jugendbuchautorinnen - Blumesberger, Susanne (2015)
The Handbook of Austrian Authors of Books for Children and Young Adults is an overview of all Austrian writers who have published at least one work for young readers. The biographical entries include information on the author’s origin, education, life history, awards, and much more. They also lend insight into each writer’s oeuvre.